Pemanfaatan Digital Marketing dalam Upaya Meningkatkan Pemasaran Produk Makanan dan Brand Awareness - Agus Supriono; Mutiara Balquis Pamuji; Evita Soleha Hani; Yuli Hariyati; Titin Agustina (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
The Covid19 pandemic has had a major impact on weakening Indonesia's economic sectors, including Small, Micro and Medium Enterprises (MSMEs). The MSME sector is one of the sectors that makes a big contribution to the national economy, so it needs to rise during the current Covid19 pandemic. Such as the problems experienced by food businesses in Kraton Village - Jember regarding the decline in turnover caused by the Covid19 pandemic. The decline in sales results was not only caused by the COVID-19 pandemic but also a lack of product marketing such as not utilizing online marketing via social media. Insufficient understanding of how to market products online is also one of the reasons for the decline in product sales during this pandemic. Seeing situations like this, it is necessary to carry out activities aimed at educating on the use of social media and optimizing business during this pandemic.